Trend diagrams of atomic relations as a tool for the chemical classification of metasomatites - Sinitsyn, V.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
A methodology is presented, and diagrams as a tool are first proposed to perform a classification of metasomatites based on chemical characteristics. The definitions of classification categories (object, subject, and criteria) for metasomatic rocks are formulated and they are compared with such categories for the rocks of another origin (metamorphic, igneous, etc.) to show the differences. The technique of plotting is described, and some application examples of the diagrams are presented. The requirements to initial data are given, and the limitations of a usage for the proposed diagrams are pointed.